Attributes in stated preference elicitation studies on colorectal cancer screening and their relative importance for decision-making among screenees: A systematic review - Melanie M. Brinkmann; Lara Marleen Fricke; Leonie Diedrich; Bernt-Peter Robra; Christian Krauth; Maren Dreier (Health Economics Review, 2022)
Introduction: The SIGMO study (Sigmoidoscopy as an evidence-based colorectal cancer screening test - a possible option?) examines screening eligible populations' preferences for colorectal cancer (CRC) screening in Germany using a discrete choice experiment (DCE). Attribute identifcation and selection are essential for the construction of choice tasks and should be evidence-based. As a part of the SIGMO study this systematic review provides an overview of attributes included in studies eliciting stated preferences for CRC screening tests and their relative importance for decision-making. Methods: Systematic search (November 2021) for English-language studies published since January 2000 in Pub- Med, Embase, Web of Science, Biomedical Reference Collection: Corporate Edition, LIVIVO and PsycINFO. DCEs and conjoint analysis ranking or rating tasks on screening eligible populations' preferences for stool testing, sigmoidos- copy, and/or colonoscopy were included. Attributes were extracted and their relative importance was calculated and ranked. Risk of bias (RoB) of included studies was assessed using a modifed GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Study selection and RoB rating were carried out independently by two reviewers. Data were extracted by one reviewer and checked by another one. Results: A total of 23 publications on 22 studies were included. Overall RoB was rated as serious/critical for 21 studies and as moderate for 2 studies. Main reasons for high RoB were non-random sampling, low response rates, lack of nonresponder analyses, and, to a lesser extent, weaknesses in the measurement instrument and data analysis. Extracted attributes (n=120) referred to procedure-related characteristics (n=42; 35%), structural characteristics of health care (n=24; 20%), test characteristics (n=23; 19%), harms (n=16; 13%), benefts (n=13; 11%), and level of evidence (n=2; 2%). Most important attributes were reduction in CRC mortality (and incidence) (n=7), test sensitivity (n=7), out-of-pocket costs (n=4), procedure (n=3), and frequency (n=2). Conclusions: Health preference studies on CRC were found to have a high RoB. The composition of choice tasks revealed a lack of attributes on patient-important outcomes (like incidence reduction), while attributes not consid- ered relevant for individual screening decisions (like sensitivity) were frequently used. Future studies eliciting stated preferences in cancer screening should apply the principles of informed decision-making in attribute identifcation and selection.
Keywords: 330; Colorectal cancer screening; Systematic review; Discrete choice experiment; Risk of bias; GRADE; Informeddecision-making